The Impact of Primary Healthcare System on Child Mortality Rates in Selected Health Organizations in North-Central Nigeria (Journal of Human Sciences, 2025)
This study aims to investigate the impact of the Primary Health Care (PHC) system in North-Central Nigeria on child mortality by analysing accessibility, affordability, and staffing in seven selected health organisations. A quantitative research design was adopted, with data collected from 700 respondents, including healthcare professionals and carers. Descriptive and inferential statistics, including mean, standard deviation, chi-square tests, and logistic regression analysis, were employed to evaluate the key variables. The findings revealed a significant negative association between PHC accessibility (p = 0.001) and child mortality, indicating that improved accessibility was linked to lower child mortality rates. Additionally, there was a significant positive association between PHC affordability (p = 0.021) and child mortality, suggesting that higher affordability was associated with reduced child mortality. For instance, data showed that for every increase in accessibility, child mortality decreased by X%, highlighting the impact of improved access on lowering child death rates. However, staffing shortages, while perceived as a major challenge, were not significantly associated with child mortality (p = 0.095). Respondents also pointed out the main obstacles to efficient service delivery, which include poor healthcare facilities and continuous medication shortages. Reducing child mortality in the region requires bettering healthcare facilities and supply chains; thus, PHC becomes more accessible and fairly priced, and overall healthcare quality is raised. Policy suggestions advocate for supporting PHC initiatives, filling shortages of healthcare professionals, and raising health insurance coverage. To gain a deeper understanding of how PHC influences child health outcomes, future studies should incorporate longitudinal data to track changes over time and consider exploring the impact of PHC on specific health indicators such as vaccination rates, maternal health, and disease prevalence in different regions of Nigeria.